ESRA19-0329 Use of pythagorean theorem to optimise needle length selection for in-plane ultrasound guided approaches to regional anaesthesia. (30th August 2019) - Beard, L; Edwards, C
Abstract : Background and aims: Selecting the ideal needle length is an important factor in successful ultrasound guided procedures: too long and the needle will be difficult to control, too short and there is a risk that the target cannot be reached. Educational materials often recommend needle lengths for procedures but obviously patients vary in size and shape. We describe a mathematical method for selecting the optimum needle length for any ultrasound transducer/target structure combination. Methods: Pythagorean theorem states that for a right-angled triangle the square of the hypotenuse is equal to the sum of the squares of the other two sides. The needle length can be calculated from the target depth and width, measured from the centre of the ultrasound probe to needle entry point, see figure 1 . Results: In general, it is best to use the shortest needle that will allow the furthest part of the target to be reached. Have in mind the maximum target depth that can be reached with a 50mm needle with the equipment you are using. You can easily calculate a table for your own equipment by measuring the distance from the centre of the probe to the edge of the probe plus 4mm working distance for needle insertion. Use this figure for value b in the formula, see table 1 . Conclusions: The application of Pythagorean theorem and production of reference table allows quick and easy selection of optimum needle length. This is useful for new trainees and in departments where a range of makes/models of ultrasound machine are used.